Risk Factors for Homelessness Among Recently Released Offenders - Karen Parhar; Stephen Wormith (Journal of Forensic Social Work, 2013)
The current study examined characteristics related to homelessness among released offenders to improve housing services for this group. Forty-one incarcerated Canadian prisoners were interviewed approximately 3 months prior to release about their former and anticipated accommodations. Homelessness prior to incarceration was positively related to violent institutional behavior, violence risk level, and criminogenic needs but not recidivism. Stable housing prior to incarceration was positively related to greater community support. Recommendations include creating more community and institutional housing programs for offenders more likely to experience housing difficulties in the community.